Analysis of the Effectiveness of Value Added Tax (VAT) Planning carried out at TAXAcc Consulting - Nugraha, Dani Oktavian; Apriliawati, Yeti (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This research was conducted at TAXAcc Consulting which states that tax consultants manage around 40-50 Corporate Taxpayer clients and around 30 Individual Taxpayer clients. Less than half of TAXAcc Consulting clients experience VAT overpayments. Even though the level of conformity between tax planning results and tax audit results is not always appropriate, TAXAcc Consulting states that tax planning is still quite effective in dealing with VAT overpayments. This research aims to determine the procedures and effectiveness of VAT tax planning carried out by TAXAcc Consulting. The research method used is qualitative, with interview techniques, documentation and literature study, to deepen understanding of the procedures and effectiveness of VAT tax planning. The results of the research are procedures used in implementing VAT tax planning consisting of tax compliance, tax review, tax litigation, tax research and tax planning. The effectiveness value for PT X was obtained at 91.66% in implementing tax planning procedures.